2017
DOI: 10.18203/2349-3291.ijcp20170425
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcome in meconium stained amniotic fluid: a hospital based study

Abstract: Background: Amniotic fluid surrounds the baby in utero and provides a protective and low resistance environment and acts as a cushion for the baby. It is secreted by amniotic membranes, foetal skin and fetal urine. The objectives of this study was to identify the incidence of meconium stained amniotic fluid, perinatal outcome and the risks during pregnancy leading to in utero passage of meconium.Methods: A prospective study conducted in Sri Guru Ram Das University, Amritsar, between 1st December 2014 to 1st Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
4
4
1
Order By: Relevance
“…In our study, 14% of patients with MSAF had postdated pregnancies. This correlated with the study conducted by Rafia et al and Singh et al in which they had 13% and 12% postdated pregnancies, respectively [ 8 , 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 14% of patients with MSAF had postdated pregnancies. This correlated with the study conducted by Rafia et al and Singh et al in which they had 13% and 12% postdated pregnancies, respectively [ 8 , 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…11 The study done by Gurmeet et al showed that 33% of the cases with MAS expired and 67% of cases with MAS were discharged, which is almost similar to the present study. 8 The number of discharged cases were more than expired cases in patients with MAS, which is similar to the present study. But all the expired cases in had severe MAS.…”
Section: Discussionsupporting
confidence: 92%
“…7 The study done by Singh G et al, showed that 76% of the neonates were more than 2.5 kg, which is higher than present study. 8 LSCS delivery was more in MSAF babies. The study done by Rokade J et al, showed that 111 patients (56%) delivered by L.S.C.S which is almost similar to present study.…”
Section: Discussionmentioning
confidence: 86%
“…Patil et al 30 reported meconium aspiration was the cause of death in around 4 cases and one died due to serve birth asphyxia with hypoxic-ischemic encephalopathy. Gurmeet Singh 31 found 16% mortality with MSAF.…”
Section: Discussionmentioning
confidence: 98%